Debt, learning and migration in the time of crisis - Kowzan, Piotr (University Electronic Press, 2020)
This paper discusses the issue of learning in adulthood by those who were indebted during the financial crisis of 2008-2009. The field research was conducted in Iceland, where interviews with indebted Icelanders and migrants were conducted, along with a broader ethnographic study. The result of the study is a model of learning based on Peter Jarvis' model, but adjusted when it comes to the context of social crisis and the possibility of migration. (DIPF/Orig.)